Granulosa cell tumors (GCTs) of the ovary: What is the role of radiotherapy?. (January 2023) - Barcellini, Amelia; Mangili, Giorgia; Fodor, Andrei; Secondino, Simona; Zerbetto, Flavia; Charalampopoulou, Alexandra; Pignata, Sandro; Orlandi, Ester; Bergamini, Alice
Abstract: Granulosa cell tumors of the ovary have an indolent behavior and a good prognosis, but a high incidence of local recurrence after surgery. The best treatment in the recurrent setting is unclear and randomized clinical trials on the management in the recurrent setting are lacking. The role of radiotherapy is controversial in adjuvant settings and unknown in case of relapse after surgery. This review aims to summarize the level of evidence of the role of radiation treatments for granulosa cell tumors of the ovary. Graphical Abstract: ga1 Highlights: Up to 25% of GCTs recur after primary surgery and mostly in the pelvis. The best treatment in the recurrent setting is unclear and randomized clinical trials for the recurrent setting are lacking. The role of adjuvant radiotherapy is controversial; radiotherapy appears feasible for unresectable and recurrent diseases. A multidisciplinary approach is of utmost importance to make a step forward in the management of recurrent settings.